State of art of real-time singing voice synthesis - Brum, Leonardo; Moreno, Edward David (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
This paper describes the state of art of realtime singing voice synthesis and presents its concept, applications and technical aspects. A technological mapping and a literature review are made in order to indicate the latest developments in this area. We made a brief comparative analysis among the selected works. Finally, we have discussed challenges and future research problems. Keywords: Real-time singing voice synthesis, Sound Synthesis, TTS, MIDI, Computer Music.